Fracture Ultrasound of the Extremities - Ackermann, Ole; Simanowski, Jörg; Eckert, Kolja (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Fracture ultrasound has increasingly come into the focus of international research. A growing number of original articles and a meta-analysis show that wrist fractures can be diagnosed without X-ray in children up to 12 years. Further original publications state that elbow fractures can be ruled out by exclusion of intraarticular effusion and in proximal humerus fractures the number of X-rays is reduced by about 50 %, while the quality of diagnosis is improved. Screening for occult fractures is another good indication. Clavicle fractures, and ac-joint sprains can be diagnosed better with US than with X-rays. A number of research groups have contributed valuable research about the different indications. The aim of this paper is to give an overview of the basics and actual fields of application for fracture ultrasound of the extremities.Die Fraktursonografie ist zunehmend Gegenstand internationaler Forschung. Die Diagnostik kann bei Kindern bis zum 12. Lebensjahr für die distale Unterarmfraktur röntgenfrei erfolgen, am Ellenbogen wird sie als Ausschlussdiagnostik angewandt und für die proximale Humerusfraktur erreicht sie eine 50 %ige Reduktion der Röntgenbelastung. Auch die Suche nach okkulten Läsionen ist eine gute Indikation; Klavikulafrakturen und AC-Sprengungen lassen sich sonografisch teilweise besser als radiologisch beurteilen. Etliche Forschungsgruppen haben in den letzten Jahren wertvolle Studien zu den verschiedenen Bereichen publiziert. Ziel dieses Beitrags ist es, dem Leser einen kompakten Überblick über die Grundlagen und aktuellen Anwendungsgebiete der Fraktursonografie der Extremitäten zu vermitteln.